Pengaruh Dividend Per Share Dan Debt To Equity Ratio Terhadap Harga Saham Pada Pt. Harum Energy, Tbk. - Jumriani, Jumriani; Sadariah, Sadariah; Asirie, Ronny Achmad (LPPM STIE Tri Dharma Nusantara - Makassar, 2024)
The purpose of this research is to determine the effect of Dividend Per Share and Debt To Equity Ratio on Share Prices at PT. Harum Energy, Tbk. The type of qualitative and quantitative data. The analytical methods used are descriptive analysis and multiple linear regression, coefficient of determination, correlation coefficient, f test, and t test. The research results of the regression equation Y = 2.102,691 + 4,338X1 – 17,674X2 coefficient of determination, R2 = 0,084 and correlation coefficient r = 0,289 simultaneously there is an insignificant influence on the Dividend Per Share and debt To Equity Ratio variables on share prices at PT. Harum Energy, Tbk. Partially, Dividend Per Share has a positive and significant influence on share prices and partially Debt To Equity Ratio has a negative and insignificant influence on share prices. Keywords: Dividend per share, debt to equity ratio, stock price.